A STUDY OF JOHN WANSBROUGH THOUGHTS ON QUR’ANIC STUDIES: SOURCE AND METHODS OF SCRIPTURAL INTERPRETATION - Azwar Sani (Sekolah Tinggi Agama Islam Sadra, 2023)
The study of Islam, particularly Quranic studies, has been shaped by various methodologies and interpretations introduced by Western scholars. Among them, John Wansbrough’s provocative insights in his methodological approach stand out. Wansbrough’s historical and literary analysis challenges traditional views by proposing that the Quran is a product of cultural evolution and influence. This article delves into Wansbrough’s perspective, focusing on his work ‘The Quranic Studies: Sources and Methods of Scriptural Interpretation.’ This study reveals Wansbrough’s arguments about the possibility of Jewish-Christian traditions in the Quran, the role of cultural contexts, and the evolution of the Quranic text. Wansbrough’s methods, including historical scepticism and literary analysis, have triggered both support and criticism. Wansbrough suggests that sacred texts, such as the Quran, may consist of different layers and undergo changes and revisions over time, especially due to cultural, political, and social influences. Although some scholars view Wansbrough’s methods as too sceptical and controversial, others consider them to provide valuable insights into the history and development of sacred texts. Scholars such as Fazlur Rahman have criticized Wansbrough’s theories, defending traditional views. However, supporters argue that Wansbrough’s ideas expand the boundaries of Quranic studies. Ultimately, this article explores and demonstrates open and critical discussions within the realm of Islamic studies, acknowledging various perspectives to achieve a deeper understanding of the complex origins and interpretations of the Quran. This research uses a qualitative approach and literature analysis to understand John Wansbrough’s thinking. Open and critical discussions are necessary for Islamic studies to understand the various perspectives and methods in uncovering the meaning of the Quran and the history of Islam.